1500 years of lake sedimentation due to fire, earthquakes, floods and land clearance in the Oregon Coast Range: geomorphic sensitivity to floods during timber harvest period. Issue 7 (8th February 2018) - Richardson, K.N.D.; Hatten, J.A.; Wheatcroft, R.A.
Abstract: Sediment cores retrieved from landslide‐dammed Loon Lake recorded events back to the 5th century AD in a forested, mountainous catchment, thereby providing an opportunity to compare the impacts of known recent perturbations, including floods and timber harvesting with those of an early period in the cores, floods, fires, and earthquakes. High‐resolution multi‐parameter (grain size, %TC, %TN, and magnetic susceptibility) data allowed the core stratigraphy to be classified as background sedimentation and events. 137 Cs and radiocarbon dating, as well as a varved record in the last 75 years provided age control. Mean mass accumulation rate from 1939 to 1978 AD, the time of peak timber harvest and a cool wet phase of the Pacific Decadal Oscillation, was 0.79 (0.74–0.92, 95% C.L.) g cm ‐2 y ‐1, significantly higher than mean rates of both the more recent contemporary period (coincident with the passing of the legislation that regulated harvesting practices in the region), 1979–2012 AD, at 0.58 (0.48‐0.70) and the entire early period, 0.44 (0.41–0.46). Several event deposits are coeval with independently estimated ages of eight Cascadia subduction zone earthquakes in the early period, including the 1700 AD Mw 9.0 event. These deposits are predominantly formed by hyperpycnal flows, as are the known event deposits in the contemporary period. The high mass accumulation rate and greater frequency of thick event deposits during the early contemporary period point to the extraordinary role of timber harvesting in priming the landscape for subsequent sedimentary delivery during floods. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Left. Age–mass model (inset graph, the y‐axis is also cumulative dry mass with all depths represented showing that the difference in estimated mean mass accumulation rates is significantly lower after better timber harvest practices were instituted in the watershed (1979–2012) compared with 1939–1978, with a difference (confidence interval) of 0.28 (0.12–0.44) g cm ‐2 y ‐1 (event free) and 0.24 (0.07–0.42) g cm ‐2 y ‐1 (all depths).Right. The relationship is shown by a scatterplot (log–log) of layer mass in the varved contemporary period and annual peak discharge (Q) at the Umpqua R. at Elkton for the water years WY 1939‐2012. The greater frequency of thick event deposits during the early contemporary period point to the extraordinary role of timber harvesting in priming the landscape for subsequent sedimentary delivery during floods.